Roadmap for Mental Health Treatment Utilizing Pharmacogenomic Testing: Case Report - Allison P. Swanson; Emily K. Mewborn; Garyung Bae (Clinical Case Reports, 2026)
Key Clinical Message Pharmacogenomic testing is a valuable precision health tool for managing depression and other mental health conditions, from treatment‐naïve patients to those with multiple medication failures. It can reduce trial‐and‐error prescribing, guide dosing, and improve therapy tolerance, supporting more individualized and effective care.